Dexterous route for synthesis of hollow spherical ZnO and ZnO-Ag nanocomposite with superior photocatalytic ability - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree (ChemistrySelect, 2019)
Hollow spherical ZnO and hollow ZnO-Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO-Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV-Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity.
Keywords: excellent photocatalysis; synthesis; template free; ZnO hollow nanoparticles; ZnO-Ag nanocomposite